DISSONANCE AND CONSONANCE BETWEEN THE COMPETITIVENESS OF - OANA CRISTINA POPOVICI; RALUCA ELENA HURDUZEU (ROTARIU) (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
The aim of this paper is to identify to what extent the notions of organizational and regional competitiveness are similar, in order to be targeted by a comprehensive set of public policy measures. In this respect, we discuss the notions of organizations’ and regional competitiveness and find common factors of influence, namely innovation, networks and regulation. Based on these factors, we search for empirical evidences as regards the mutual impact between the competitiveness of organizations and competitiveness of regions. We present the results using the example of foreign direct investment companies, as their location decision making process is based on assessing both the competitiveness of organizations and the advantages of locations that point to the competitiveness of a location and, extended, to that of a region. While the dissonance is expressed in the differences of interpretation for the two notions, there is a consonant policy that can be employed for supporting both organizational and regional competitiveness: the cluster policy.